Internalization of Character Values in Through the Learning of Ta'līm Al-Muta'allim Book - Naim, Ainun; Sariman, Sariman (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The success of education is marked by outputs that lead to the realization of morality and character formation in real life. Religious knowledge is part of the process of internalizing the character of students. This study uses a descriptive qualitative approach. Aims to describe, and analyze the planning, implementation, and internationalization model of character values through learning Ta'lim Al Muta'alim at Madrasah Nurul Muttaqin Bojonegoro. As primary data sources are the head of the madrasah, waka curriculum, and teachers, data collection through participatory observation, in-depth interviews, and documentation. Data analysis through data collection, condensation, data display, and data verification. The results of this study are as follows: (1) The planning includes; a) material, b) objectives, c) learning methods, and d) needs analysis in learning. (2) The process of internalizing character values through learning the book of Ta'lim Al-Mut'allim uses three stages: 1) Value transformation. At this stage, the focus is on understanding the value material in the Ta'lim Al-Mut'allim book. 2) Value transaction occurs two-way reciprocal interaction between students and teachers actively. 3) Character trans-internalization stage. At this stage, the teacher and students begin to correlate the character values in the Kitab Ta'lim Al-Mut'allim, which can be implemented in real life. (3) The internalization model of character values through learning the book of Ta'lim Al-Mut'allim using the Tadzkiroh model, (2) Istiqomah Model, (3) Iqra-Fikir-Dhikr Model.